The relationship between recognised intangible assets and voluntary intellectual capital disclosure. Issue 2 (14th September 2015) - Schiemann, Frank; Richter, Kai; Günther, Thomas
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The capitalisation of intangible investments is discussed controversially in the financial accounting literature. International accounting standards are concerned with this issue and generally demand more intellectual capital to be recognised on the face of the balance sheet. If investors and analysts already gather monetary information about intangible assets from the financial report and find such information useful, then the necessity to complement such information with voluntary intellectual capital disclosure will diminish. Accordingly, there should be an association between recognised intangible assets and voluntary intellectual capital disclosure. The paper aims to discuss these issues. Design/methodology/approach – The authors analyse the voluntary disclosure of 264 investor conference and roadshow presentations of German DAX 30 firms in the year 2001, 2003, 2005, and 2007. The authors apply regression models to analyse the association between recognition of intangible assets and voluntary intellectual capital disclosure and control for other determinants of voluntary disclosure. Findings – The authors find that the magnitude of recognised intangible assets is significantly and negatively associated with the quantity and quality of voluntary intellectual capital disclosure. The authors show that this association is mainly driven by goodwill accounting. In more detailed analyses we find different directions (positive, negative and insignificant) of this relationship for different categories of intellectual capital. Research limitations/implications – Future studies on voluntary intellectual capital disclosure need to consider recognised intangible assets as a determinant to avoid omitted variable problems. Practical implications – The authors provide descriptive evidence about voluntary intellectual capital disclosure practice of Germany's largest firms. Originality/value – The paper provides primary evidence on the association between recognised intangible assets and voluntary intellectual capital disclosure.